Statistical analysis of carbonate looping process feasibility - Hanak, Dawid P.; Michalski, Sebastian; Manovic, Vasilije (Cranfield University, 2018)
Data produced during the statistical evaluation of the techno-economic feasibility of CaL concepts using data available in the current literature
Keywords: 'calcium looping'; 'carbonate lopping'; 'feasibility assessment'; 'carbon capture'; 'Energy Generation; Conversion and Storage Engineering'; 'Power and Energy Systems Engineering (excl. Renewable Power)'; 'Carbon Capture Engineering (excl. Sequestration)'